2019
DOI: 10.1590/0103-8478cr20180242
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and sensory evaluation of meat from cobia (rachycentron canadum), desensitized with different voltages of electric shock, stored under refrigeration

Abstract: Fish quality is conditioned by several factors, among them desensitization methods applied for fish managing and slaughtering. This research used electric shock at different intensities as a desensitization method for cobia (Rachycentron canadum) slaughtering and evaluated its effects over fish quality during refrigerated storage. The experiment was carried out by numbing the fish with electroshock at the intensities of 100, 150 and 200 Volts, and keeping them in refrigerated storage for 21 days. On the cobia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In the present study, a slower pH decrease was observed in meat samples from fish submitted to recovery periods after transport, while samples from fish collected right after harvesting and after transport presented lower pH values at time 0, confirming that the postmortem biochemical changes occurred more accelerated for these treatments according to reported by Oliveira-Filho (2021), who observed low pH levels after 5 hours of pacu slaughter using different slaughter methods. Melo et al (2018) also observed a decrease in muscle pH in tilapia slaughtered by different electronarcosis voltages after 5 hours of slaughter. Erickson et al (2016) also observed lower initial pH values in stressed Atlantic cod when compared to the control.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, a slower pH decrease was observed in meat samples from fish submitted to recovery periods after transport, while samples from fish collected right after harvesting and after transport presented lower pH values at time 0, confirming that the postmortem biochemical changes occurred more accelerated for these treatments according to reported by Oliveira-Filho (2021), who observed low pH levels after 5 hours of pacu slaughter using different slaughter methods. Melo et al (2018) also observed a decrease in muscle pH in tilapia slaughtered by different electronarcosis voltages after 5 hours of slaughter. Erickson et al (2016) also observed lower initial pH values in stressed Atlantic cod when compared to the control.…”
Section: Discussionmentioning
confidence: 66%